Language Competence Formation Among VETI NRNU MEPhI Students in the View of State Corporation «Rosatom» Export-Oriented Policy - Zarochintseva, I. V.; Zakharova, L. V.; Lupinogina, Yu. A.; Bunames, N. V.; Kolesnikova, E. V. (Глобальная ядерная безопасность, 2022)
The paper is devoted to the formation of language competence within the framework of a communication-oriented approach in the light of the requirements of the State Atomic Energy Corporation «Rosatom». The paper discusses a competence-based approach that focuses on the organization of educational and cognitive activities. It presents the experience of using modern communication technologies, Internet resources, online services. The ways of improving the learning process are proposed. The competencies acquired as a result of learning a foreign language are considered.